Ornament as a need in spontaneous architecture. Learning aesthetics from self-constructed dwellings. - Dreifuss Serrano, Cristina (2015)
Investigación presentado en el "European Symposium on Research in Architecture and Urban Design - EURAU '10", realizado en Naples, Italia, del 23 al 26 de Junio del 2010.